1994
DOI: 10.1007/bf02357777
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit memory for catastrophic associations to bodily sensation words in panic disorder

Abstract: This study investigated explicit (cued recall) and implicit memory (word completion) memory bias for catastrophic associations among individuals with panic disorder (n = 24), clinician controls (n = 24), and normal controls (n = 24). Compared to both control groups, the panic disorder group showed biased explicit and implicit memory for catastrophic associations to bodily sensation words (e.g., palpitation-coronary) compared to positive (e.g., smiles-elation) and neutral (e.g., groceries-coupons) word pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
3
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 33 publications
1
32
3
1
Order By: Relevance
“…This clearly contrasts with assumptions of all previous studies known to us examining attentional or memory biases in clinical disorders using symptom-specific stimuli (e.g. Amir et al, 1996;Becker et al, 1994;Cloitre et al, 1994;Ehlers et al, 1988b;Rapee, 1994). Moreover, it is important to note that our hypothesis does not imply that patients with panic disorder show enhanced implicit memory performance.…”
Section: Assumptions and Aims Of The Present Studycontrasting
confidence: 79%
See 1 more Smart Citation
“…This clearly contrasts with assumptions of all previous studies known to us examining attentional or memory biases in clinical disorders using symptom-specific stimuli (e.g. Amir et al, 1996;Becker et al, 1994;Cloitre et al, 1994;Ehlers et al, 1988b;Rapee, 1994). Moreover, it is important to note that our hypothesis does not imply that patients with panic disorder show enhanced implicit memory performance.…”
Section: Assumptions and Aims Of The Present Studycontrasting
confidence: 79%
“…Thus, patients with anxiety disorders were presumed to display a tendency to selectively detect, focus on, interpret, store, and retrieve threat-related information. In concordance with this hypothesis, patients with panic disorder were found to show shorter response latencies to the presentation of threatening words (Asmundson, Sandler, Wilson, & Walker, 1992), to evaluate panic-related auditory information as more intense than neutral information (Amir, McNally, Rieman, & Clements, 1996), and to show enhanced implicit and explicit memory performance for bodily sensation words (Cloitre, Shear, Cancienne, & Zeitlin, 1994; but see also Rapee, 1994).…”
Section: Clinical Approachesmentioning
confidence: 65%
“…Cloitre et al [13] found a memory bias in an implicit memory task performed by patients with panic disorder prior to therapy. This memory bias was no longer apparent after successful psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, using incidental learning tasks, found a memory bias for explicit but not for implicit memory [11], others found a bias in implicit but not in explicit memory [12]. Again others found a bias for both implicit and explicit memory [13], whereas, for example, Rapee [14] did not find a memory bias for either implicit or explicit memory.…”
Section: Introductionmentioning
confidence: 99%
“…magazine) words, whereas normal control subjects exhibited no di¡eren-tial memory as a function of word valence. Cloitre et al (1994) exposed panic patients, clinicians experienced in treating panic disorder, and normal controls to pairs of words that were either related or unrelated, and were either negative, positive or neutral in valence. Thus, breathless^su¡ocate' was a related threat word-pair, and`cheerful^bureau' was an unrelated positive wordpair.…”
Section: E Mot Ion -C Ong Ru E N T M E Mory Bi a Smentioning
confidence: 99%